Evaluation Of Artvin Government House In The Context of Modern Architectural Heritage - Koray Güler; Ayşe Ceren Bilge (Megaron, 2016)
Artvin, which had been a view of a rural town in the first years of the Turkish Republic, had still preserved its traditional character in this era. Over time a major transformation lasted in town's traditional character that can be seen in many other Anatolian towns. In addition to the change that took place in the city's residential areas, so many public buildings are added to the urban lanscape in time because of being the central of the province. Artvin Government House is the most important one beetween these buildings which has built in 1974 by winning architectural project of Aslaner, Güngören and Gürel after the competition of Ministry of Public Works in 1968 according to the need of a new Goverment House. Old government house which was an important witness of the city's history and was expected to be protected from competitors were transferred to the new building with the creation of an abstract modulation in the proportions of the new design. Despite all the efforts the historical building was demolished in the 1980s. This study aimed to discuss the conservation of modern architectural heritage subject, which has started to be more discussed in conservation science environments in recent years, in the case of Artvin Government House which carries traces of the old government house. The protection of Artvin Government House, which was obtained after a national architectural competition, has a crucial importance because of not only reflects the architectural style of the period but also witnesses the town's last fourty years history. The preservation of the 20th century modern architectural heritage of Artvin and transmitting to this heritage to next generations are at least important that the protection of the traditional and monumental buildings dating to 19th century or earlier periods that number of which are decreasing nowadays.